Design, development and construction of a medical wrist rehabilitation device - Seabra, Eurico (2018)
This project consisted on the design, development and construction of a medical device for the rehabilitation of the wrist. The construction of the actual prototype was carried out with off-the-shelf components. The objective was to develop a functional and low cost device. The system is divided into two main components, one for the rehabilitation of the wrist and the other one to perform proprioception exercises, providing relaxation of the patient’s pain due to injuries on the wrist. All the hardware is assembled in one portable support, capable to carry out vertical and horizontal adjustments. Both systems are fully controlled through a software specially designed for being used by both physiotherapists and patients, allowing at the same time the control over the progress of rehabilitation.